Laborde Cabezas,Wendy Vanessa(2023)GESTIÓN INTEGRAL SOSTENIBLE DE RESIDUOS ALIMENTARIOS EN EL SECTOR HOTELERO DEL CANTÓN QUEVEDO, PROVINCIA DE LOS RÍOS.Quevedo.UTEQ.113p. - Laborde Cabezas , Wendy Vanessa (2023)
The hotel industry is an important economic activity worldwide, but its production of solid waste, such as organic waste, plastics, paper and cardboard, can have a negative impact on the environment. In the canton of Quevedo, 24 hotels generate 63% of the waste in the area, including food waste, plastics, cardboard, glass, and organic waste. Lack of compliance with environmental requirements and poor supervision are contributing factors. In addition, inefficient management of the municipality's garbage collectors contributes to the contamination of streets and sidewalks. The study identified significant environmental impacts, such as soil contamination, loss of fauna and risk to human health. A sustainable approach to solid waste management in tourist accommodations is proposed, developing a tool for its evaluation and recommending its reduction, reuse, and recycling. Hotel workers should also be trained in proper waste management and the active participation of guests and clients in sustainable waste management should be encouraged. Proper food waste management not only benefits the environment, but can also generate economic opportunities for hotels through recycling and composting, and improve the image and reputation of the business. It is important to consider that the management of solid waste generated by the hotel industry not only affects the community, but also the business, so it is essential to act in a responsible and sustainable manner.